Tyrosol and Hydroxytyrosol: Their Role in Cardioprotection - Guzowski, Cezary; Murawska, Joanna; Michalska, Martyna; Winiarek, Karolina; Czernicka, Aleksandra; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2024)
Introduction: Recent research are focused on natural compounds for preventing cardiovascular diseases, with emphasis on tyrosol and hydroxytyrosol in olive oil. Cardiovascular diseases are linked to risk factors, and adopting a Mediterranean diet rich in these compounds is recognized for reducing risks. Understanding these compounds’ actions may inform new strategies for preventing and treating cardiovascular diseases. Aim: The aim of this paper is a systematic review of articles and research regarding the Role of tyrosol and hydroxytyrosol in Cardioprotection Review methods: An systematic review of scientific literature was conducted using the following keywords: Tyrosol, hydroxytyrosol, cardioprotection, cardiovascular diseases, olive oil cardioprotective role. Thirty-four articles published until 2023 were searched and analyzed. Abbreviated description of the state of knowledge: Tyrosol and hydroxytyrosol, prominent in olive oil, are studied for their potential cardioprotective properties. Linked to a Mediterranean diet, these compounds show promise in reducing cardiovascular disease risk. They counter oxidative stress, improve lipid profiles, and modulate inflammatory processes. Clinical studies suggest their positive impact, with tyrosol also explored as a potential anticoagulant. Ongoing research aims to uncover optimal doses and mechanisms, highlighting their significance in cardiovascular health. Conclusions: Tyrosol and hydroxytyrosol, found in olive oil, show promise in cardioprotection by combating oxidative stress, improving lipid profiles, and modulating inflammation. Clinical studies suggest their positive impact on cardiovascular health. Tyrosol has potential as a anticoagulant and exhibits antioxidant effects. These compounds present a compelling avenue for future therapeutic interventions, with emphasis on understanding mechanisms and optimizing supplementation.